Answer:
Using the above algorithm matches one pair of Ghostbuster and Ghost. On each side of the line formed by the pairing, the number of Ghostbusters and Ghosts are the same, so use the algorithm recursively on each side of the line to find pairings. The worst case is when, after each iteration, one side of the line contains no Ghostbusters or Ghosts. Then, we need n/2 total iterations to find pairings, giving us an P(
)- time algorithm.
Answer:
a) 2,945 mC
b) P(t) = -720*e^(-4t) uW
c) -180 uJ
Explanation:
Given:
i (t) = 6*e^(-2*t)
v (t) = 10*di / dt
Find:
( a) Find the charge delivered to the device between t=0 and t=2 s.
( b) Calculate the power absorbed.
( c) Determine the energy absorbed in 3 s.
Solution:
- The amount of charge Q delivered can be determined by:
dQ = i(t) . dt
![Q = \int\limits^2_0 {i(t)} \, dt = \int\limits^2_0 {6*e^(-2t)} \, dt = 6*\int\limits^2_0 {e^(-2t)} \, dt](https://tex.z-dn.net/?f=Q%20%3D%20%5Cint%5Climits%5E2_0%20%7Bi%28t%29%7D%20%5C%2C%20dt%20%3D%20%5Cint%5Climits%5E2_0%20%7B6%2Ae%5E%28-2t%29%7D%20%5C%2C%20dt%20%3D%206%2A%5Cint%5Climits%5E2_0%20%7Be%5E%28-2t%29%7D%20%5C%2C%20dt)
- Integrate and evaluate the on the interval:
![= 6 * (-0.5)*e^-2t = - 3*( 1 / e^4 - 1) = 2.945 C](https://tex.z-dn.net/?f=%3D%206%20%2A%20%28-0.5%29%2Ae%5E-2t%20%3D%20-%203%2A%28%201%20%2F%20e%5E4%20-%201%29%20%3D%202.945%20C)
- The power can be calculated by using v(t) and i(t) as follows:
v(t) = 10* di / dt = 10*d(6*e^(-2*t)) /dt
v(t) = 10*(-12*e^(-2*t)) = -120*e^-2*t mV
P(t) = v(t)*i(t) = (-120*e^-2*t) * 6*e^(-2*t)
P(t) = -720*e^(-4t) uW
- The amount of energy W absorbed can be evaluated using P(t) as follows:
![W = \int\limits^3_0 {P(t)} \, dt = \int\limits^2_0 {-720*e^(-4t)} \, dt = -720*\int\limits^2_0 {e^(-4t)} \, dt](https://tex.z-dn.net/?f=W%20%3D%20%5Cint%5Climits%5E3_0%20%7BP%28t%29%7D%20%5C%2C%20dt%20%3D%20%5Cint%5Climits%5E2_0%20%7B-720%2Ae%5E%28-4t%29%7D%20%5C%2C%20dt%20%3D%20-720%2A%5Cint%5Climits%5E2_0%20%7Be%5E%28-4t%29%7D%20%5C%2C%20dt)
- Integrate and evaluate the on the interval:
![W = -180*e^-4t = - 180*( 1 / e^12 - 1) = -180uJ](https://tex.z-dn.net/?f=W%20%3D%20-180%2Ae%5E-4t%20%3D%20-%20180%2A%28%201%20%2F%20e%5E12%20-%201%29%20%3D%20-180uJ)